Rising Powers and Normative Resistance: China, India, and the Responsibility to Protect. Issue 141 (4th May 2023) - Fung, Courtney J.
ABSTRACT: What explains rising powers' approach to emerging norms that challenge ontological order? The article uses a controlled comparison of two rising powers, China and India, as they address the responsibility to protect, which reconceives state sovereignty as contingent. Both states rejected the norm at its inception, before diverging as UN Security Council members during norm application in the Libya intervention. China assumed a creative resister role, offering tactical concessions, while using traditional sovereignty norms to renovate norm content. India assumed a norm begrudger role, typified by rhetorical rejection and disengagement from evolving normative discourse, coupled with practical support for the responsibility to protect. These rising powers' normative roles are shaped by their dual status and differing positions within the UN Security Council social environment.